In vitro Protective Effect of Rutin and Quercetin against Radiation-induced Genetic Damage in Human Lymphocytes - Patil, Shrikant L. (Indian J Nucl Med, 2017)
PURPOSE OF THE STUDY: Rutin (RUT) and quercetin (QRT) which are dietary compounds were investigated for their ability to protect against ionizing radiation (IR)-induced genotoxicity in human lymphocytes. MATERIALS AND METHODS: The radiation antagonistic potential of RUT and QRT was assessed by alkaline comet and cytokinesis-block micronucleus (CBMN) assay. RESULTS: Treatment of lymphocytes with RUT and QRT (25 μg/ml) prior exposure to 2 Gy gamma radiation resulted in a significant reduction of frequency of micronuclei as compared to the control set of cells evaluated by CBMN assay. Similarly, treatment of lymphocytes with RUT and QRT before radiation exposure showed significant decrease in the DNA damage as assessed by comet parameters, such as percent tail DNA and olive tail moment. CONCLUSION: The study demonstrates the protective effect of RUT and QRT against IR-induced DNA damage in human lymphocytes, which may be partly attributed to scavenging of IR-induced free radicals and also by the inhibition of IR-induced oxidative stress.